Integrating philosophy, policy and practice to create a just and fair health service. Issue 12 (7th October 2020) - Fritz, Zoe; Cox, Caitríona L
Abstract : To practise 'fairly and justly' a clinician must balance the needs of both the many and the few: the individual patient in front of them, and the many unseen patients in the waiting room, and in the county. They must consider the immediate clinical needs of those in the present, and how their actions will impact on future patients. The good medical practice guidance 'Make the care of your patient your first concern' provides no guidance on how doctors should act when they care for multiple patients with conflicting needs. Moreover, conflicting needs extend far past simply those between different patients. At an organisational level, financial obligations must be balanced with clinical ones; the system must support those who work within it in a variety of roles; and, finally, in order for a healthcare service to be sustainable, the demands of current and future generations must be balanced. The central problem, we propose, is that there is no shared philosophical framework on which the provision of care or the development of health policy is based, nor is there a practical, fair and transparent process to ensure that the service is equipped to deal justly with new challenges as they emerge. Many philosophers have grappled with constructing a set of principles which would lead to a 'good' society which is just to different users; prominent among them is Rawls. Four important principles can be derived using a Rawlsian approach: equity of access, distributive justice, sustainability and openness. However, Rawls' approach is sometimes considered too abstract to be applied readily to policymaking; it does not provide clear guidance for how individuals working within existing institutions can enact the principles of justice. We therefore combine the principles derived from Rawls with Scanlonian contractualism: by demanding that decisions are made in a way which cannot be 'reasonably rejected' by different stakeholders (including 'trustees' for those who cannot represent themselves), we ensure that conflicting needs are considered robustly. We demonstrate how embedding this framework would ensure just policies and fair practice. We illustrate this by using examples of how it would help prevent injustice among different socioeconomic groups, prevent intergenerational injustice and prevent injustice in a crisis, for example, as we respond to new challenges such as COVID-19. Attempts to help individual doctors practise fairly and justly throughout their professional lives are best focused at an institutional or systemic level. We propose a practical framework: combining Scanlonian contractualism with a Rawlsian approach. Adopting this framework would equip the workforce and population to contribute to fair policymaking, and would ultimately result in a healthcare system whose practice and policies—at their core—were just.